Cytochemical characterization of the endomembranous system during oocyte secondary growth in Serrasalmus spilopleura (Teleostei, Characiformes, Characidae) - Guimaraes, A. C. D.; Quagio-Grassiotto, I. (Blackwell Publishing, 2008)
The endomembranous system of Serrasalmus spilopleura oocyte secondary growth was analysed using structural and ultrastructural cytochemical techniques. In vitellogenic oocytes, the endoplasmic reticulum components, the nuclear envelope intermembranous space, some Golgi dictiossomes, lysosomes, yolk granules, regions of the egg envelope and sites of the follicle cells react to acid phosphatase detection (AcPase). The cortical alveoli, some heterogeneous cytoplasmic structures, regions of the egg envelope, and sites of the follicle cells are strongly contrasted by osmium tetroxide and zinc iodide impregnation (ZIO). The endoplasmic reticulum components, some vesicles, and sites of the follicle cells also react to osmium tetroxide and potassium iodide impregnation (KI). The biosynthetic pathway of lysosomal proteins, such as acid phosphatase, required for vitellogenesis, involves the endoplasmic reticulum, Golgi complex, vesicles with inactive hydrolytic enzymes, and, finally, lysosomes. In S. spilopleura oocytes at secondary growth, the endomembranous system takes part in the production of the enzymes needed for vitellogenesis, and in the metabolism of yolk exogenous components (AcPase detection). The endomembranous system compartments also show reduction capacity (KI reaction) and are involved in the metabolism of proteins rich in SH-groups (ZIO reaction).
Keywords: structural and ultrastructural cytochemistry; acid phosphatase; oocyte; Serrasalmus spiloleura